PENGEMBANGAN E-COMIC SEBAGAI MEDIA PEMBELAJARAN IPS PADA MATERI ORGANISASI PERGERAKAN NASIONAL INDONESIA DI MTS. NEGERI 1 KOTA BEKASI (Sosiolium: Jurnal Pembelajaran IPS, 2023)
Circular Regulation (SE) of the Minister of Education and Culture Number 2 of 2022 which regulates Hybrid learning, which is limited face-to-face learning of 50% of the total class capacity of 100% and interspersed with online learning. The online learning system is the same as in MTs. Negeri 1 Bekasi City, one of the obstacles experienced was a lack of understanding of social studies material due to time constraints. Developing e-comic as an online learning medium for students can help students understand social studies material well when learning online, the need for e-comic as an online learning medium for social studies subjects is 76.7%.The research method uses Research and Development (R&D) in accordance with the rules of steps according to Borg and Gall and adapts to the needs of researchers, the steps include: potential and problems, preparation and data collection stages, product design, product testing stages by students and validators, product improvement, field trial phase, implementation.The steps of development include: (1) Reviewing KI-KD and GPA, (2) Determining materials and titles, (3) Storyline with dialogue scripts, (3) Story Board, (3) Digitization, (4) Uploading. The results of media eligibility: (1) The results of the media expert validation obtained a score of 93% in the very appropriate category, (2) The results of the material expert validation obtained a score of 82% in the very feasible category, (3) The response to the trial of using a small scale obtained a score of 78% in the good category, (4) Responses to the use of large-scale trials of class 8.1 and 8.2 after being revised each obtained a score of 94% in the very good category. Thus the e-comic media in the material for the Indonesian national movement organization is very suitable for use by students during the online learning process. Suggestions, e-comic can be developed better in the form of real stories from the material of the Indonesian national movement organization and overall using digitization techniques with software, it is necessary to introduce material to be studied and information on procedures for using e-comic, especially how to access and download, and media e-comic can be tested further to find out its effectiveness. Surat Edaran (SE) Mendikbud Nomor 2 tahun 2022 yang mengatur pembelajaran Hybrid, yaitu melakukan pembelajaran tatap muka secara terbatas 50% dari total kapasitas kelas 100% dan diselingi dengan pembelajaran daring. Sistem pembelajaran daring sama halnya dilakukan di MTs. Negeri 1 Kota Bekasi, kendala yang dialami salah satunya adalah kurang paham dengan materi IPS karena keterbatasan waktu. Mengembangkan e-comic sebagai media pembelajaran daring untuk peserta didik dapat membantu memahami materi IPS dengan baik saat belajar daring, kebutuhan e-comic sebagai media pembelajaran daring mata pelajaran IPS sebanyak 76,7%. Metode penelitian menggunakan Research and Development (R&D) sesuai dengan kaidah langkah menurut Borg and Gall dan menyesuaikan dengan kebutuhan peneliti, langkah-langkahnya meliputi: potensi dan masalah, tahap persiapan dan pengumpulan data, desain produk, tahap uji coba produk oleh peserta didik dan validator, perbaikan produk, tahap uji coba lapangan, implementasi. Tahap pengembangan desain diantaranya: (1) Mengkaji KI-KD dan IPK, (2) Menebtukan materi dan judul, (3) Alur cerita dengan skrip dialog (3) Story Board, (3) Digitasi, (4) Uploading. Hasil kelayakan media: (1) Hasil validasi ahli media memperoleh skor 93% kategori sangat layak, (2) Hasil validasi ahli materi memperoleh skor 82% kategori sangat layak, (3) Tanggapan uji coba penggunaan skala kecil memperoleh skor 78% kategori baik, (4) Tanggapan uji coba penggunaan skala besar kelas 8.1 dan 8.2 setelah direvisi masing-masing memperoleh skor 94% kategori sangat baik. Dengan demikian media e-comic pada materi organisasi pergerakan nasional Indonesia sangat layak digunakan oleh peserta didik selama proses pembelajaran daring. Saran, e-comic dapat dikembangkan lebih baik lagi berupa cerita sesungguhnya dari materi organisasi pergerakan nasional Indonesia dan keseluruhan menggunakan teknik digitasi dengan software, perlu adanya perkenalan materi yang akan dipelajari dan informasi tata cara menggunakan e-comic terutama cara akses dan mengunduh, dan media e-comic dapat diujicobakan lebih lanjut untuk mengetahui keefektifannya.